IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) - Ismail, Ernawati; Igirisa, Irawaty; Kamuli, Sukarman (Jambura Journal of Administration and Public Service, 2025)
Ernawati Ismail, 941419002, 2025. Implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) Policy in Suwawa Selatan Sub-district, Bone Bolango Regency. Undergraduate Thesis, Study Program of Public Administration, Universitas Negeri Gorontalo. The Principal Supervisor is Dr. Irawaty Igirisa, S.Pd., M.Si. and the co-supervisor is Dr. Sukarman Kamuli, M.Si. This research aimed to analyze the implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) policy in Suwawa Selatan Sub-district, Bone Bolango Regency, and to identify the factors determining its success. It employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, direct observation, and document study, then analysed using data reduction, data display, and conclusion drawing. The results showed that the implementation of the BSPS policy consists of three main stages: planning, implementation, and reporting. Planning followed the existing procedures, but obstacles remain in delivering information to the community. The implementation stage ran moderately effective with the support of field facilitators, although it faced challenges such as delays in building materials and limited labour. At the reporting stage, the procedures were carried out properly, with the reports prepared by the community under the guidance of field facilitators (TFL). The determining factors for successful program implementation include communication, resources, implementers’ disposition, and bureaucratic structure. Among these factors, resources were the most dominant and influential, leading to the smooth progress of physical construction. Overall, the implementation of BSPS in Suwawa Selatan Sub-district is considered relatively effective, but improvements in outreach program and strengthening of supporting resources are still needed to achieve more optimal results.